2016
DOI: 10.1002/hbm.23224
|View full text |Cite
|
Sign up to set email alerts
|

LSD alters eyes‐closed functional connectivity within the early visual cortex in a retinotopic fashion

Abstract: The question of how spatially organized activity in the visual cortex behaves during eyes-closed, lysergic acid diethylamide (LSD)-induced "psychedelic imagery" (e.g., visions of geometric patterns and more complex phenomena) has never been empirically addressed, although it has been proposed that under psychedelics, with eyes-closed, the brain may function "as if" there is visual input when there is none. In this work, resting-state functional connectivity (RSFC) data was analyzed from 10 healthy subjects und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 63 publications
(76 reference statements)
3
48
1
Order By: Relevance
“…This within-area stability is in contrast to the variability in betweenarea interactions observed in previous studies (Heinzle et al, 2011;Raemaekers et al, 2014;Butt et al, 2013;Gravel et al, 2014). Whereas between-area interactions are less stable during RS, during VFM they become more stable (Gravel et al, 2014;Arcaro et al, 2015;Heinzle et al, 2011;Roseman et al, 2016), giving rise to a synchronization-based structure that is consistently found across subjects (as shown by Fig. 5).…”
Section: Phase-synchronization-based Parcellation Of Rs Fmri Signals contrasting
confidence: 55%
“…This within-area stability is in contrast to the variability in betweenarea interactions observed in previous studies (Heinzle et al, 2011;Raemaekers et al, 2014;Butt et al, 2013;Gravel et al, 2014). Whereas between-area interactions are less stable during RS, during VFM they become more stable (Gravel et al, 2014;Arcaro et al, 2015;Heinzle et al, 2011;Roseman et al, 2016), giving rise to a synchronization-based structure that is consistently found across subjects (as shown by Fig. 5).…”
Section: Phase-synchronization-based Parcellation Of Rs Fmri Signals contrasting
confidence: 55%
“…This is supported by a recent neuroimaging study (Carhart-Harris et al 2016), which showed that LSD-induced simple and complex hallucinations were closely related to LSD-induced activation of the primary visual cortex. This is further supported by mathematical modelling (Bressloff et al 2002, Ermentrout andCowan 1979) and behavioural (Baggott et al 2010) and neuroimaging (Roseman et al 2016, Araujo et al 2012 showing that psychedelic-induced excitation of the primary visual cortex may facilitate spontaneous formation of retinotopically organised geometric hallucinations, which in turn could progress to more complex scenic hallucinations by spreading up the visual hierarchy.…”
Section: Cognitive Bizarreness and Basic Visual Processingmentioning
confidence: 86%
“…In addition to physiology research supporting the presence of these connections (also reviewed in §8), additional support comes from the ability of certain drugs like LSD to induce synaesthesia in non-synaesthetic adults in a transient fashion [14]. Human neuroimaging research shows increased resting state activity in the visual cortex following LSD induction compared with placebo control [111,112], indicating that psychedelic drugs may give rise to synaesthetic experiences by increasing the basal neural activity in the visual cortex, which in turn could lead to stochastic resonance between the inducer and the visual cortex. If cross-sensory anatomical connections are present and functionally relevant in the general population, then why are not all individuals synaesthetes?…”
Section: Evidence Supporting the Stochastic Resonance Modelmentioning
confidence: 99%
“…Similarly, certain drugs induce specific cortical changes (e.g. LSD alters levels of neural noise and connectivity in visual cortex [111,116]). Thus, one should be able to track drug-induced cortical excitability changes in a modality-specific manner to predict the onset and type of synaesthesia induced.…”
Section: Future Directionsmentioning
confidence: 99%